Communication peculiarities in Spanish and English cultures - Kabanova S. S. (Human and society, 2017)
the article reveals the question of communication peculiarities in Spanish and English cultures using an example of comparison and collation of verbal and nonverbal linguistic behavior; describes cultural values and their expression in the language. The research is based on historic, geographic and climate components and perception of time, that are responsible for national and cultural specificity of expression and exchange of thoughts and help to avoid misunderstanding in the process of communication.
Keywords: ценности; коммуникация; язык; специфика; время; communication; Language; values; time; reality; действительность; peculiarity